Influence of HMD Type and Spatial Ability on Experiences and Learning in Place-based Education - Sajjadi, Pejman; Zhao, Jiayan; Wallgrun, Jan Oliver; Femina, Peter La; Klippel, Alexander (2021 7th International Conference of the Immersive Learning Research Network (iLRN), 2021)
With the emergence of different types of Head-Mounted Displays (HMDs), researchers and educators must make informed decisions on what HMDs best support their needs. When performing experiments with relatively large populations, these decisions are largely affected by the sensing-scaling tradeoff between high-end tethered HMDs and lower-end standalone systems. Higher sensing affords a richer experience, but it is also associated with higher costs in terms of the HMD itself and the need for VR-ready computers. These limitations often impede instructors from using high-end HMDs in an efficient way with larger populations. We report on the results of a study in the context of place-based immersive VR (iVR) Geoscience education that compares the experiences and learning of 45 students after going through an immersive virtual field trip, using either a lower-sensing but scalable Oculus Quest or a higher-sensing but tethered HTC Vive Pro. Our results indicate that students who used the Quest reported significantly higher levels of satisfaction but also more simulator sickness (although still a very low number on average) compared to those who used an HTC Vive Pro. Our findings suggest that with content design considerations, standalone HMDs can be a viable replacement for high-end systems in large-scale studies. Furthermore, our results also suggest that in the context of place-based iVR education, the spatial abilities of students (i.e., sense-of-direction) can be a determining factor in their experiences and learning, and therefore an important topic of study for designing effective place-based iVR experiences.